2019
DOI: 10.1186/s13063-019-3407-3
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a multi-centre pilot and feasibility randomised controlled trial with a nested qualitative study: rehabilitation following rotator cuff repair (the RaCeR study)

Abstract: Background Shoulder pain is a highly prevalent complaint and disorders of the rotator cuff, including tears, are thought to be the most common cause. The number of operations repair the torn rotator cuff has risen significantly in recent years. While surgical techniques have progressed, becoming less invasive and more secure, rehabilitation programmes have remained largely like those initially developed when surgical techniques were less advanced and more invasive. Uncertainty remains in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…To date, there is limited evidence to suggest whether or not an accelerated rehabilitation approach is effective in patients with PHF. Similar research comparing early/accelerated rehabilitation to delayed rehabilitation following rotator cuff repair has been reported (Houck, Kraeutler, Schuette, McCarty, & Brayman, 2017; Littlewood et al, 2019; Mazuquin et al, 2018; Sheps et al, 2015, 2019) and it has been found that early mobilisation might speed up recovery following rotator cuff repair. In this context, there is an urgent need to carry out high‐quality research to better inform practice and optimise clinical outcomes for patients following PHF.…”
Section: Discussionsupporting
confidence: 62%
“…To date, there is limited evidence to suggest whether or not an accelerated rehabilitation approach is effective in patients with PHF. Similar research comparing early/accelerated rehabilitation to delayed rehabilitation following rotator cuff repair has been reported (Houck, Kraeutler, Schuette, McCarty, & Brayman, 2017; Littlewood et al, 2019; Mazuquin et al, 2018; Sheps et al, 2015, 2019) and it has been found that early mobilisation might speed up recovery following rotator cuff repair. In this context, there is an urgent need to carry out high‐quality research to better inform practice and optimise clinical outcomes for patients following PHF.…”
Section: Discussionsupporting
confidence: 62%
“…The group supported the co-production of patient-facing materials and development of study processes such as recruitment and informed consent. They also had a patient representative as part of their trial management group [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The group supported the co-production of patient-facing materials and development of study processes such as recruitment and informed consent. They also had a patient representative as part of their trial management group (35).…”
Section: Resultsmentioning
confidence: 99%